Perbedaan Penguasaan Konsep Biologi Siswa SMA Jurusan IPS Berbasis Gender dengan Menggunakan Model Project Based Learning - Harisanti, Baiq Muli; Fatmawati, Any; Hajiriah, Titi Laily; Karmana, I Wayan (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2024)
Mastery of concepts in a field of science includes a combination of mastery of knowledge of the field of science being studied and dimensions of cognitive processes, including factual, conceptual and procedural knowledge. The importance of students' mastery of concepts related to the field of biology means that teachers must continue to train students to master biological concepts well. In general, social studies students have good knowledge in the field of social studies, but not necessarily good knowledge in the field of science, especially biology. The aim of this research is to reveal gender-based mastery of biology concepts of students majoring in social studies at SMA Negeri 7 Mataram using a project based learning model. The research method used quasi correlational involving 126 students, consisting of 45 male students and 81 female students. Data analysis used an independent sample t test at a significance level of 5%. The research results show that there is no significant difference between male and female students' mastery of concepts using the project based learning model. The average mastery of concepts for male students is 56.296, and the average mastery of concepts for female students is 57.510. The significance value (Sig. 2 tailed) is 0.618 > 0.05. The implication of this research is that the project based learning model does not provide a significant difference in students' mastery of concepts based on gender, or the project based learning model can be said to have the same effect in increasing students' mastery of biology concepts, both for male and female students.